Effect of Pore Geometry on Nanoconfined Bulk-Gas Flow Behavior - Yi Zhang (Geofluids)
In order to improve energy consumption structure in Guizhou province, China, the efficient development of shale gas becomes more and more important. However, the theoretical understanding, towards microscopic gas flow mechanism, is still weak and insufficient. Although many models have been established, one part of them fails to cover all flow mechanisms, and the other part contains several fitting parameters. Moreover, nanopores can be divided into circular pore and slit pore in accordance with pore geometry. For cylindrical nanopores, by fully comparing with the existed models, a new bulk-gas transport model is proposed by weight superposition of slip flow and Knudsen diffusion, in which weight factors are obtained by Wu’s model and Knudsen’s model, respectively. For slit pores, an analytical equation for bulk-gas flow is proposed as well, which is free of any fitting parameters. The reliability of the proposed models has been clarified. The impacts of reservoir pressure, pore scale, and gas flow mechanism on bulk-gas flow behavior in process of shale gas development are analyzed. It is found that gas transport capacity of slit nanopores is significantly higher than that of cylindrical nanopores at the same pore scale. For slit nanopores, the larger the aspect ratio, the stronger bulk-gas transmission capacity. As the established models are free of fitting parameters and can be applied into the entire Kn range with sufficient accuracy, the research will greatly benefit shale gas development.